Endotracheal tube placement confirmation: 100% sensitivity and specificity with sustained four-phase capnographic waveforms in a cadaveric experimental model. (June 2017) - Silvestri, Salvatore; Ladde, Jay G.; Brown, James F.; Roa, Jesus V.; Hunter, Christopher; Ralls, George A.; Papa, Linda
Abstract: Background: Waveform capnography is considered the gold standard for verification of proper endotracheal tube placement, but current guidelines caution that it is unreliable in low-perfusion states such as cardiac arrest. Recent case reports found that long-deceased cadavers can produce capnographic waveforms. The purpose of this study was to determine the predictive value of waveform capnography for endotracheal tube placement verification and detection of misplacement using a cadaveric experimental model. Methods: We conducted a controlled experiment with two intubated cadavers. Tubes were placed within the trachea, esophagus, and hypopharynx utilizing video laryngoscopy. We recorded observations of capnographic waveforms and quantitative end-tidal carbon dioxide (ETCO2 ) values during tracheal versus extratracheal (i.e., esophageal and hypopharyngeal) ventilations. Results: 106 and 89 tracheal ventilations delivered to cadavers one and two, respectively (n = 195) all produced characteristic alveolar waveforms (positive) with ETCO2 values ranging 2–113 mmHg. 42 esophageal ventilations (36 to cadaver one and 6 to cadaver two), and 6 hypopharyngeal ventilations (4 to cadaver one and 2 to cadaver two) all resulted in non-alveolar waveforms (negative) with ETCO2 values of 0 mmHg. Esophageal and hypopharyngeal measurements were categorized as extratracheal (n = 48). A binary classification test showed no false negatives or false positives, indicating 100% sensitivity (NPV 1.0, 95%CI 0.98–1.00) and 100% specificity (PPV 1.0, 95%CI 0.93–1.00). Conclusion: Though current guidelines question the reliability of waveform capnography for verifying endotracheal tube location during low-perfusion states such as cardiac arrest, our findings suggest that it is highly sensitive and specific.